An Analysis of The Ability of The Second Semester Students of Public Administration on Learning English By Applying Google Classroom - Napitupulu, Merlin Helentina (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
This research deals with the ability of the second-semester students of Public Administration in Academic Year 2019/2020 on Learning English by applying Google Classroom. This research applied Google Classroom during pandemic Covid 19. It was conducted at Universitas Timor, Nusa Tenggara Timur. This research applied a qualitative descriptive method that describes the students of the public administration’s ability on learning English about Basic English Grammar. The population of this research was the second-semester students of the Public Administration of Universitas Timor.  There were six classes of the second-semester public administration students who took English subjects. The sample was taken by applying cluster sampling and the students from class A were chosen as the sample.  The result shows that the students’ ability on learning English is at a good level even though the student should learn English from home by applying Google Classroom during pandemic Covid-19.